c. \( 3 \times 2-3 \times 1=(3 \times 2)-(3 \times 1)=(33(2-1) \) If \( a=3, b=2 \) and \( c=4 \), calculate the following: Example: \( \quad a(b+c)=a \times b+a \times c \) \( 3(2+4)=3 \times 2+3 \times 4 \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Mind Expander
Let's break this down using the values you provided! First, we have: \( a(b+c) = a \times b + a \times c \) Substituting \( a = 3 \), \( b = 2 \), and \( c = 4 \): \( 3(2+4) = 3 \times 2 + 3 \times 4 \) Calculating this step-by-step: Left side: \( 3(6) = 18 \) Right side: \( 3 \times 2 = 6 \text{ and } 3 \times 4 = 12 \) So, \( 6 + 12 = 18 \) Thus, \( 3(2+4) = 3 \times 2 + 3 \times 4 \) holds true! Now for your equation: \( 3 \times 2 - 3 \times 1 = (3 \times 2) - (3 \times 1) = 3(2 - 1) \) Let’s compute this: Left side: \( 3 \times 2 = 6 \text{ and } 3 \times 1 = 3 \) So, \( 6 - 3 = 3 \) Right side: \( 3(2 - 1) = 3(1) = 3 \) Both sides match, confirming that \( 3 \times 2 - 3 \times 1 = 3(2 - 1) \) is also correct!